Nickel-Catalyzed Decarboxylative Coupling of Alkynyl Carboxylates with Aryl Tosylates and Mesylates - Howard, Anna; Klemann, Samantha; Kolling, Sarah; Little, Katrina; Plasek, Erin; Kalyani, Dipannita (Synthesis, 2019)
A method for the nickel-catalyzed coupling of alkynyl carboxylates or acids with aryl tosylates and mesylates is described. Electronically varied carboxylates and aryl electrophiles participate in these transformations to afford the desired diarylalkyne products. In general, electrophiles bearing an extended π-system lead to products in higher yields than sulfonates with only one aromatic ring.
Keywords: alkynes; arenes; carboxylic acids; cross-coupling; nickel catalysis; decarboxylative